Role of the epithelium in human papillomavirus and human immunodeficiency virus infections in the female genital tract - Sibeko, Sengeziwe; Sanderson, Micheline; Moyo, Sizulu; Botha, Matthys H. (Frontiers in Reproductive Health, 2024)
Background: Two-thirds of people living with human immunodeficiency virus type 1 (HIV-1) infection reside in sub-Saharan Africa, where there are the highest prevalence and incidence rates of human papillomavirus (HPV) infection. Both infections are sexually transmitted and enter the body via the epithelium. This review describes the extent of involvement of the epithelium in each infection in the female genital tract. Methods: A narrative review was conducted on the role of the epithelium in HPV and HIV-1 infections. Results: An intact epithelial barrier is the predominant form of protection against viral entry and infection, including from HIV-1 and HPV. HPV is an intraepithelial pathogen, and thus, its growth and amplification, which are dependent on squamous cell differentiation, occur in the epithelium. It gains entry to the basal cells of the stratified squamous epithelium via microabrasions or other epithelial injuries that expose the basement membrane. HIV-1, conversely, passes through the epithelium to infect subepithelial tissues. Following deposition of the HIV-1-containing inoculum into the lumen, the virus enters the mucosa through breaks in the epithelial barrier within hours of infection. Further, HIV-1 penetrates the epithelium via various mechanisms, including paracellular passage or across epithelial cells through transcytosis. The capture of the virus from the mucosal surface by intraepithelial and/or subepithelial target cells has also been documented. Conclusions: Epithelial disruption is the major pathogenetic pathway in HIV-1 and HPV infections.Therefore, biochemical compounds that strengthen the epithelial barrier must be prioritized to prevent these infections.